(untitled) (Bioscience Journal, 2021)
The reproductive efficiency of livestock is the basis for the success of livestock, dairy or beef, and having high reproductive performance depends on several factors within the production system and the presence of infectious diseases of the reproductive sphere in the herd is one of the factors that can compromise that efficiency. The aim of this study was to use molecular biology as a diagnostic tool for the detection of Leptospira spp. DNA in cows with reproductive disorders on a rural property in the municipality of Boca do Acre, Amazonas, Brazil. Vaginal mucus was collected from nine Nelore breeding cows with a history of abortion and birth of weak calves submitted to DNA extraction and nested-PCR technique for 16S gene amplification at the bacterial genus level. Of the nine samples analyzed, five (55.55%) amplified a product of 331bp. The municipality of Boca do Acre is bordered by Peru and Bolivia, and knowledge of the prevalence of the disease, serovars, and circulating Leptospira species is essential for the adoption of measures related to animal husbandry, as well as health education for ranchers and their workers to avoid a possible occupational infection since this disease is considered an important zoonosis. New molecular studies using primers that allow the identification of the Leptospira species and mainly pathogenic species should be conducted in this region in order to elucidate the possible species of this etiological agent and the possible reservoirs of the disease to begin the understanding of the epidemiology of this disease in cattle in this region of border.